The Role of Community in Shaping Children's Moral Education in Batee Shok, Sabang City - Mahliati (Lembaga KITA, 2023)
This research explores the role of the community in fostering moral education for children in Batee Shok, Sabang City, Indonesia, and identifies the challenges hindering optimal moral development. The study investigates the educational landscape, considering factors such as community collaboration, moral education practices, available resources, mentorship, and the societal environment. The findings highlight that the community's efforts in Batee Shok are not fully optimized for effective moral education. While advice is provided to children, there is a notable absence of setting good examples and engaging in essential Islamic activities. The study identifies several obstacles, including the lack of community attention and collaboration, insufficient moral education within the community, limited resources for Islamic educational activities, scarcity of qualified mentors, and an unfavorable societal environment. To address these challenges, the research recommends increased community involvement, setting positive examples, and active engagement in moral education initiatives. Additionally, local leaders and influential figures are encouraged to play a more active role in shaping the moral landscape for children in Batee Shok. Furthermore, collaboration with governmental institutions is suggested to enhance resources and support for Islamic educational activities. These recommendations aim to improve the quality and effectiveness of moral education programs for children in Batee Shok.